The Effect of Therapeutic Communication on the Anxiety Level of Children Undergoing the COVID-19 Vaccination - Naufal, Irfan Hanif; Harnanto, Addi Mardi; Sunarto, Sunarto; Widodo, Widodo; Sudiro, Sudiro (JKG (JURNAL KEPERAWATAN GLOBAL), 2023)
Background: Anxiety is often encountered in society, especially in children, when undergoing the COVID-19 vaccination. Anxiety is a factor influencing children to refuse vaccination. Therefore, nurses need to reduce this level of anxiety through the application of therapeutic communication. This research was carried out to determine the effect of therapeutic communication on children's anxiety levels during the implementation of the COVID-19 vaccination. Methods: A pre-experiment design with a one-group pretest-posttest design was used on 58 respondents who were selected using a simple random sampling technique. The research instrument used was the Zung Self-Rating Anxiety Scale (SAS/SRAS) questionnaire with a Likert scale model, and the results were analyzed using the Wilcoxon Signed Ranks Test statistical test. Results: The results of the Wilcoxon Signed Ranks Test analysis on respondents' anxiety levels showed that there was a decrease in anxiety after therapeutic communication was carried out with a p-value of 0.00 (p < 0.05), which means that therapeutic communication had a significant influence on the anxiety level of children undergoing the COVID-19 vaccination. Conclusion: Therapeutic communication can effectively reduce the anxiety level of children undergoing COVID-19 vaccination.